(untitled) (Publicaciones en Ciencias y Tecnología, 2011)
This article aims to show the advantages of fuzzy logic as a tool to support decision making in light of bioethical principles, in turn, encourage fellow researchers to continue research on the development of this promising area namely in the light of the complexity of reality. The methodology was a literature review by authors from first and second order and the application of the technique of focus group leaders to collect the data. Introduces concepts such as fuzzy logic, complexity, ethics, religation ethics, bioethics are introduced, and their interaction in decision making. Within the results highlight the applicability of the fuzziness in the process of managerial decision making where the main actor is the individual within a complex environment.